Casper's scare school - Baily, Evan, ]e production; Guggenheim, Ralph; Walters, Sandra; Gravas, Mark ([New York, N.Y.] : Classic Media, 2007)
Casper goes to school so he can frighten humans, but instead uses what he learns to save the world from some nasty demons
Based on the comic character created by Seymour Reit and Joe Oriolo
Title from title screen
Screenplay by Andrew Nicholls, Darrell Vickers ; story by Kirk De Micco, Robert Mittenthal
Voices: Devon Werkheiser, Dan Castellaneta, James Belushi, Bob Saget, Phyllis Diller
dvd Format
With English, Chinese and Malay subtitles
Keywords: Reit, Seymour -- Film and video adaptations; Oriolo, Joe -- Film and video adaptations; Casper the Friendly Ghost (Fictitious character) -- Drama; Ghosts -- Drama; Animated films; Monsters -- Drama; Good and evil -- Drama